A newly modified nerve-sparing radical hysterectomy technique with analysis of short-term oncologic, surgical, and functional outcomes - Han, Shichao; Wang, Xinyou; Zhu, Jinming; Li, Ya; Na, Jing; Wang, Jun (Frontiers in Oncology, 2025)
ObjectiveThis study aims to investigate a newly modified approach to nerve-sparing radical hysterectomy.Subjects and MethodsPathological large-section staining of the entire paracolpium from specimens obtained after radical hysterectomy was performed to examine its structural composition and identify the course and distribution of the pelvic plexus and its branches. Based on the analysis of nerve pathways and locations, a total of 55 cases of modified nerve-sparing surgeries preserving pelvic autonomic function were conducted.ResultsAll radical hysterectomies were performed in accordance with the principles of membrane anatomy. Postoperative pathological large-section staining of the paracolpium, combined with microscopic examination, revealed three distinct planes from ventral to dorsal: a vascular plane, consisting of the deep uterine vein and bladder venous plexus draining into the deep uterine vein; a neural plane, formed by the pelvic plexus and its nerve branches; and a ligamentous plane, consisting of the sacral ligament. In clinical practice, utilizing the three-plane structure of the paracolpium and medially lifting the vascular plane facilitated safe, reliable dissection, exposure, and preservation of pelvic autonomic nerve function.Through clinical practice, follow-up, and analysis of 55 cases, it was observed that combining the concept of membrane anatomy with the three-plane anatomical structure of the paracolpium not only enables nerve-sparing radical hysterectomy as a bloodless surgical procedure but also ensures optimal nerve preservation, favorable oncological outcomes, and a significant reduction in perioperative complications.ConclusionGuided by the principles of membrane anatomy and the three-plane theory of the paracolpium, nerve-sparing radical hysterectomy facilitates precise preservation of pelvic autonomic nerve function in a bloodless manner, while achieving favorable oncological outcomes.